Arthropods in Different Vegetation in Nutmeg Plantation in Aceh Province - Muhammad Sayuthi; Hasnah Hasnah (The Faculty of Veterinary Medicine of Syiah Kuala University, 2021)
Nutmeg (Myristica fragrans Hout) is a leading commodity from Aceh Province. The high yield of nutmeg oil and its distinctive aroma makes it in demand by the world market. The production of nutmeg plants is currently decreasing due to the disturbance of nuisance organisms so that nutmeg plants get sick and die. Appropriate agro eco-management of the nutmeg system is thought to overcome these problems. Such as by conserving the diversity of arthropod communities. Information regarding the presence of arthropods in nutmeg cultivation is very limited in South Aceh District. This study investigates the abundance of arthropods in nutmeg cultivation in different vegetation to detect the causes of the decline in nutmeg production in the South Aceh district. Sampling was carried out at 2 locations with different vegetation conditions, using the determining sub-samples. Each location consisted of 200 individual nutmeg plants, and at each location, several 20 individual nutmeg plants were assigned as samples. The results showed that the total collection of arthropod populations at the location I found nine orders, namely Araneae, Coleoptera, Dermaptera, Diptera, Homoptera, Hemiptera, Hymenoptera, Isoptera, and Orthoptera. Location II found 12 orders, namely Araneae, Blattodea, Coleoptera, Dermaptera, Diptera, Embioptera, Homoptera, Hemiptera, Hymenoptera, Isoptera, Orthoptera, and Phasmatodea). The class of insects and arachnids found at these two locations is part of the Phylum Arthropoda.